GRAVITY MODELING OF HARUMAN FAULT AT THE EAST BOUNDARY OF BANDUNG BASIN - Lina Handayani; Dadan D. Wardhana; Yayat Sudrajat (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2012)
ABSTRACT Bandung area, as one of most populated area in Indonesia and one region with a high risk of earthquake hazard, needs a comprehensive mitigation work. To locate active faults is one of the most important things in preliminary survey for earthquake hazard mitigation effort. Accordingly, two transect lines of gravity measurement were completed across a suspected active fault, Haruman Fault, at the east of Bandung Basin region. The subsurface modeling has presented a general idea of geological subsurface structure of this transects area and indicates the possible existences of faults at the east boundary of Bandung-Garut Basin.